Risk factors for inadequate bowel preparation: a validated predictive score - Gimeno-García, Antonio Z.; Baute, Jose Luis; Hernandez, Goretti; Morales, Dalia; Gonzalez-Pérez, Carmen Delia; Nicolás-Pérez, David; Alarcon-Fernández, Onofre; Jiménez, Alejandro; Hernandez-Guerra, Manuel; Romero, Rafael; Alonso, Inmaculada; Gonzalez, Yanira; Adrian, Zaida; Carrillo, Marta; Ramos, Laura; Quintero, Enrique (Endoscopy, 2017)
Background and study aim Inadequate bowel cleansing negatively affects the efficiency of colonoscopy in routine clinical practice. The aim of this study was to design and validate a predictive model for inadequate bowel cleanliness.Patients and methods The model was built from 667 consecutive outpatients (development cohort) who were prospectively scheduled for colonoscopy between June and September 2014. The validation cohort included 409 outpatients who underwent colonoscopy between October and December 2014. Cleansing was evaluated using the Boston Bowel Preparation Scale (BBPS). Bowel preparation was administered on the same day as the examination.Results In the development cohort, BBPS was adequate in 541 patients (81.1 %). At multivariate analysis, antidepressants (odds ratio [OR] 4.25, 95 % confidence interval [CI] 1.91 – 9.47), co-morbidity (OR 3.35, 95 %CI 2.16 – 5.18), constipation (OR 2.09, 95 %CI 1.29 – 3.40), and abdominal/pelvic surgery (OR 1.60, 95 %CI 1.03 – 2.47) were independent predictors for inadequate cleansing. The model built with these variables showed an area under the curve of 0.72 in the development cohort and 0.70 in the validation cohort. A cutoff of 1.225 predicted inadequate bowel preparation with a sensitivity, specificity, positive predictive value, and negative predictive value of 60.3 % (95 %CI 51.6 – 68.4), 75.4 % (95 %CI 71.6 – 78.9), 36.4 % (95 %CI 30.1 – 43.1), and 89.1 % (95 %CI 85.9 – 91.6) in the development cohort, and 50.0 % (95 %CI 38.1 – 61.9), 80.0 % (95 %CI 75.3 – 84.2), 35.7 % (95 %CI 26.4 – 45.6), and 87.9 % (95 %CI 83.7 – 91.3) in the validation cohort.Conclusion A simple score may assist the clinician in predicting which patients are at high risk of inadequate bowel cleanliness. This may guide changes in bowel preparation strategy accordingly.